Ozone (O3) observations in Saxony, Germany, for 1997–2020: trends, modelling and implications for O3 control - Y. Wang; D. van Pinxteren; A. Tilgner; E. H. Hoffmann; M. Hell; S. Bastian; H. Herrmann (Atmospheric Chemistry and Physics)
Given its importance for human health, vegetation and climate, trends in ground-level ozone (O3) concentrations in eastern Germany were systematically analysed using the long-term O3 data from 16 measurement stations. The findings indicate that despite reductions in oxides of nitrogen (NOx= NO + NO2) concentrations across all sites, O3 pollution in Saxony has in fact worsened over the past decade, especially in densely populated urban areas. The strongest O3 trend is observed at a traffic-dominated station, with an annual ozone increase of 1.2 µg m−3 yr−1 (or 3.5 % yr−1), while urban and rural background stations show more moderate rises of, on average, 0.5 µg m−3 yr−1 (or 1.1 % yr−1) over the last decade.